catena-Poly[cobalt(II)-bis(μ-2-aminoethanesulfonato)-κ3N,O:O′;κ3O:N,O′] - Xu-Hui Liu (Acta Crystallographica Section E, 2010)
The hydrothermally prepared title compound, [Co(C2H6NO3S)2]n, is isotypic with its NiII analogue. The CoII cation is in a distorted octahedral environment, coordinated by four sulfonate O atoms and two N atoms from the taurine ligands. In comparison with the NiII analogue, the Co—N and Co—O bonds are longer than the Ni—N and Ni—O bonds, whereas all other bond lengths and angles as well as the hydrogen-bonding motifs are very similar in the two structures. The sulfonate groups doubly bridge symmetry-related CoII atoms, forming polymeric chains along the a axis. N—H...O hydrogen bonding interactions consolidate the crystal packing.